The other frontiers of Arab nationalism: Ibadis, berbers, and the Arabist-Salafi Press in the Interwar period - Ghazal, Amal N. (International Journal of Middle East Studies, 2010)
On Abū Isḥāq Ibr. Iṭfayyish (Cairo), Abū ‘l-Yaqẓān Ibr. (Mīzāb), Hāshil al-Maskarī and his journal al-Falaq in Zanzibar.
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Aṭfiyyash; Ibrāhīm b. Muḥammad (1886-1965); Maskarī; Hāshil al-; Réformisme

Islamic reform and Arab nationalism: expanding the crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Ghazal, Amal N. (Routledge, 2010)
This book examines the relationship between Islam and nationalism and the evolution of identity politics. Bridging African and Arab histories and giving a cross-national and cross-regional analysis of movements of religious reform, nationalism and anti-colonialism, its wide geographical coverage ranges from Zanzibar on the Indian Ocean through to Oman into the Mediterranean
Don de l'auteure
Keywords: Zanzibar